Effects Of Structural Complexity On The Distribution Of Macrobenthos At Selected Artificial And Natural Shorelines In Penang Island, Malaysia - Adam, Amni Nabilah Mat (2017)
The aim of this research is to study the diversity of macrobenthos and relationship of structural complexity to these organisms. The study was done on the rocky shores of Penang Island. Thirty quadrats with dimension 15 cm x 15 cm were photographed monthly in six different sites with three sites each for natural and artificial habitat from January 2016 to April 2016 at three different shore levels along a 25 m transect line parallel to shoreline. Physicochemical water parameters were measured in-situ while nutrients and heavy metals were sent to the laboratory for testing. To measure structural complexity, the average individual number of ecosystem engineers, Saccostrea cucullata, Amphibalanus amphitrite and Chthamalus malayensis were counted based on quadrat photos.